Strength Analysis On Materials Used In Unconventional Wet Mix Macadam Of An Asphalt Pavement - Mudigonda Harish Kumar, Dr.C.Freeda Christy (International Journal of Advanced Science and Technology, 2020)
The main aim of this research is to make an effective use of waste Fly ash, stone dust &tyre rubber to stabilize the wet mix macadam. Rubber tire waste is produced in large amounts worldwide. It cannot be degraded easily. Burning of it releases harmful gases takes much time and also causes environmental pollution by releasing carbon when discarded. Stone dust is a by product of quarries. It is produced in very large quantities. Some amount of this is used for making flower pots and other petty things. Large content of it is been dumped in yards which affects the quality of the soil. By using stone dust, fly ash and tyre powder in the construction of pavements some of the waste product is reused from disposing so that it contribute a little benefit to environment. In this experimental, two unconventional mixes in wet mix macadam (WMM) of an asphalt pavement were considered.Mix1 is the combination of stone dust, epdm rubber & fly ash, Mix2 is the combination of fly ash & tyre rubber. After preparing the mix, CBR test has been performed and the results were compared with conventional WMM.